The Berenstain bears and the slumber party - Berenstain, Stan; Berenstain, Jan (New York : Random House, 1990)
Lizzy Bruin's slumber party becomes even wilder when Too-Tall Grizzly and his friends decide to attend uninvited.
Keywords: Children's stories